Why are Online Games Addictive? A Study on The Relationship Between Game Features and Social Perspectives - Nugroho Hardiyanto; Iwan Mulyawan; Mohammad Rizal Gaffar (JEMBATAN, 2022)
The rapid development of online games makes online games very popular. This study aims to analyze the factors that make a person addicted to playing online games. This research analyses game features and social perspectives that influence online game addiction. Respondents in this study are online game players in Indonesia with 340 respondents. The analysis technique used is PLS-SEM. The results showed that game features had a significant effect on game addiction. Social factors such as social presence and social capital contributed to game addiction. This research can be information on the factors that influence game addiction from game features and social perspectives.